2006
DOI: 10.1093/rpd/ncl402
|View full text |Cite
|
Sign up to set email alerts
|

Experimental fragmentation studies with 12C therapy beams

Abstract: High-energy beams of (12)C ions in the range of 80-430 MeV u(-1) delivered by the heavy-ion synchrotron SIS-18 are used for radiotherapy of deep-seated localized tumors at the treatment unit at GSI Darmstadt. In order to improve the physical database, the fragmentation characteristics along the penetration path in tissue were investigated experimentally by using a water phantom as tissue-equivalent absorber. Measurements were performed at specific energies of 200 and 400 MeV u(-1) of the incident (12)C ions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
116
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 6 publications
(3 reference statements)
4
116
0
Order By: Relevance
“…The Monte Carlo calculations were performed both with and without taking into account nuclear fragmentation reactions. Experimental data by Schardt et al [16] are also shown for comparison. Our calculated position of the Bragg peak is about 5 mm (2%) deeper than predicted by simulations and observed by the experiment.…”
Section: Ion Passage Through the Mediummentioning
confidence: 96%
See 1 more Smart Citation
“…The Monte Carlo calculations were performed both with and without taking into account nuclear fragmentation reactions. Experimental data by Schardt et al [16] are also shown for comparison. Our calculated position of the Bragg peak is about 5 mm (2%) deeper than predicted by simulations and observed by the experiment.…”
Section: Ion Passage Through the Mediummentioning
confidence: 96%
“…Indeed, it is estimated [17] as 5-15% of the total projectile energy loss. [16] So far our consideration neglects the fact that the projectile energy loss is a stochastic process, and |dT /dx| was calculated as the average LET. Therefore, we introduced the energy-loss straggling which essentially improves the agreement with the MCHIT results obtained taking into account the stochastics of energy-loss process.…”
Section: Ion Passage Through the Mediummentioning
confidence: 99%
“…Instead, we choose to fit the parameterization with measurements of the LET dependence on the penetration depth in liquid water. These depths have been measured at GSI [24,25]. This not only provides several curves at different initial energies, but also a direct comparison with the carbon ion data.…”
Section: B Semi-empirical Model Extensions For Liquid Watermentioning
confidence: 99%
“…[25] and MC simulations [22] (where no nuclear fragmentation is considered). The zoom in the inset shows also the experimental penetration depth.…”
Section: B Semi-empirical Model Extensions For Liquid Watermentioning
confidence: 99%
“…Another example are the light fragments produced beyond the Bragg peak in tissues when hadron beams of carbon or neon at 200 400 MeV/u are used in radiotherapy [2]: the knowledge of the dierential cross-sections of various fragments in medical applications is mandatory to constrain treatment plan codes and to spare doses to healthy tissues.…”
mentioning
confidence: 99%